Notes on the lesser white-lined bat, Saccopteryx leptura (Schreber) (Chiroptera, Emballonuridae), from southeastern Brazil - Nogueira,Marcelo R. (2002)
Saccopteryx leptura (Schreber, 1774) is reported from two new localities in southeastern Brazil, both in Atlantic forest remains in the state of Rio de Janeiro. Analysisof food material showed that individuals from both localities had preyedon insects in the order Hymenoptera. Cheek contents were available from one specimen, and in this case identification of the food item (flying ants) achieved generic level (Pheidole Westwood, 1841). Aspects in the social behavior observed in a colony suggest that the same traits documented in Central American populations (small colonies, monogamic mating system, and retention of young for up to a year in the parental unit) may also characterize this species in the southern most part of its range. In both external and craniodental selected measurements, specimens from Rio de Janeiro were close to the upper limits of the ranges known for the species.